Upaya Meningkatkan Hasil Belajar Siswa Kelas III SD Negeri 39 Lubuklinggau dalam Pembelajaran IPA tentang Gerak Benda melalui Metode Demonstrasi - Susilawati Susilawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effort to improve the learning outcomes of third grade students of SD Negeri 39 Lubuklinggau in science learning about the motion of objects through demonstration methods. This classroom action research consists of three cycles. The preliminary research was conducted on April 3, 2015, cycle 1 on April 10, 2015 and cycle II on April 17, 2015 with the following results; 1) student activity from prasiklus, cycles 1, and cycle 2 increased by 24.14 on prasiklus, 51.72 in cycle I and 86.21 in cycle II, 2) individual completeness also increased, 53.45% in prasiklus, and 64.48% in cycles I and 75.35 in cycle II, 3) classical completeness also increased, ie 37.24% in prasiklus, and 62.07% in cycles I and 82.76 in cycle II. Conclusion in the research is the implementation of demonstration method can increase student's learning interest, thus encouraging student learning outcomes in Class III State Elementary School 39 Lubuklinggau Keywords: Learning Outcome, Demonstration Method, Science Lesson